β-catenin-independent noncanonical Wnt pathway might be induced in gastric cancers - Salih GENCER; Gürkan ŞEN; Gülen DOĞUSOY; Ahmet Korkut BELLİ and Melih PAKSOY and M. Burcu Irmak YAZICIOĞLU (Turkish Journal of Gastroenterology, 2019)
-